Narrativas de familiares de usuários de um Centro de Atenção Psicossocial sobre o cuidado em saúde mental - Pizano, Juliana Peixoto [UNESP] (2015)
The care network in Brazilian mental health is part of the Unique Health System (SUS). With the Psychiatric Reform process, several substitute care services to those with psychological distress and needs resulting from crack, alcohol and other drugs were implanted. The Psychosocial Care Center (CAPS) is one of these services and it has a strategic role being the responsible of articulation care along with the Primary Care. The CAPS objective is to offer attendance to users and family in psychosocial perspective. Family is, mostly, principal responsible for the care, therefore CAPS must develop strategies for better serve it in their needs together the person with psychological distress. It‟s required to consider family in its historicity and social nature, understand its part and functioning in current society, as well the relationships established in it. This dissertation intends to comprehend the family mental health care and the meanings attributed to mental illness process by relative‟s users CAPS. The theoretical framework is from Historical-Cultural Psychology, based on the understanding of reality from historical materialist and dialectical. Fifteen family members were invited to participate in this survey: eight didn‟t attend the scheduled interviews and seven were performed (one of those couldn‟t be transcribed). The results showed as center part of illness process: 1) Pregnancy and popular beliefs; 2) Resentment; 3) Accumulation of experiences and situation limit. Others signification nucleus are related to every day care: 1) Pray; 2) Talk; 3)Clean and monitor; 4) Tire; 5)Contradict. Thus, we identified the importance of CAPS workers know the care process in families and help by building new strategies to deal with suffering and the impact on the family group